2018
DOI: 10.1093/mnras/sty552
|View full text |Cite
|
Sign up to set email alerts
|

Dusty galaxies in the Epoch of Reionization: simulations

Abstract: The recent discovery of dusty galaxies well into the Epoch of Reionization (redshift z > 6) poses challenging questions about the properties of the interstellar medium in these pristine systems. By combining state-of-the-art hydrodynamic and dust radiative transfer simulations, we address these questions focusing on the recently discovered dusty galaxy A2744 YD4 (z = 8.38, Laporte et al. 2017). We show that we can reproduce the observed spectral energy distribution (SED) only using different physical values wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
193
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 139 publications
(209 citation statements)
references
References 104 publications
(142 reference statements)
13
193
3
Order By: Relevance
“…Using MAGPHYS (da Cunha et al 2008), we can give a first constraint on the dust temperature in this object T dust > 55 K. This value contrasts with the value generally used to determine the dust properties at high-z (T∼30K), but is consistent with recent simulations (e.g. Behrens et al 2018) which predict a higher dust temperature at high redshifts. Using the 3σ upper limits for both band 5 and 6 observations decreases the minimum dust temperature to T>43 K.…”
Section: Discussionsupporting
confidence: 82%
“…Using MAGPHYS (da Cunha et al 2008), we can give a first constraint on the dust temperature in this object T dust > 55 K. This value contrasts with the value generally used to determine the dust properties at high-z (T∼30K), but is consistent with recent simulations (e.g. Behrens et al 2018) which predict a higher dust temperature at high redshifts. Using the 3σ upper limits for both band 5 and 6 observations decreases the minimum dust temperature to T>43 K.…”
Section: Discussionsupporting
confidence: 82%
“…The average 13 radiation field is G = (7.9 ± 23.1) G0 i.e. compatible with the assumption in Pallottini et al (2017b), where G = G0(SFR/M yr −1 ) (see also Behrens et al 2018). Note that the variance of the radiation field is 3 times the mean, as in the MW (Habing 1968;Wolfire et al 2003).…”
Section: Freesia Structural Propertiessupporting
confidence: 73%
“…Aoyama et al (2017) found that the assumption of fixed dust-tometal ratio is no longer valid once galaxies are older than 0.2 Gyr. Behrens et al (2018) found in simulations that the dust-to-metal ratios for galaxies at z ∼ 8 are only 0.08, i.e. far lower than the value in the local Universe.…”
Section: Dust Model Calibrationmentioning
confidence: 77%